Core genome multilocus sequence typing scheme for Bacillus cereus group bacteria - Tourasse, Nicolas J.; Jolley, Keith A.; Kolstø, Anne-Brit; Økstad, Ole Andreas (Research in microbiology, 2023)
Core genome multilocus sequence typing (cgMLST) employs a strategy where the set of orthologous genes common to all members of a group of organisms are used for phylogenetic analysis of the group members. The Bacillus cereus group consists of species with pathogenicity towards insect species as well as warm-blooded animals including humans. While B. cereus is an opportunistic pathogen linked to a range of human disease conditions, including emesis and diarrhoea, Bacillus thuringiensis is an entomopathogenic species with toxicity toward insect larvae, and therefore used as a biological pesticide worldwide. Bacillus anthracis is a classical obligate pathogen causing anthrax, an acute lethal condition in herbivores as well as humans, and which is endemic in many parts of the world. The group also includes a range of additional species, and B. cereus group bacteria have been subject to analysis with a wide variety of phylogenetic typing systems. Here we present, based on analyses of 173 complete genomes from B. cereus group species available in public databases, the identification of a set of 1568 core genes which were used to create a core genome multilocus typing scheme for the group which is implemented in the PubMLST system as an open online database freely available to the community. The new cgMLST system provides unprecedented resolution over existing phylogenetic analysis schemes covering the B. cereus group.